2018
DOI: 10.1016/j.solmat.2017.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of doped nanocrystalline silicon oxide for applications in silicon thin-film and heterojunction solar cells

Abstract: To optimize the optical response of a solar cell, specifically designed materials with appropriate optoelectronic properties are needed. Owing to the unique microstructure of doped nanocrystalline silicon oxide, nc-SiO x :H, this material is able to cover an extensive range of optical and electrical properties. However, applying nc-SiO x :H thin-films in photovoltaic devices necessitates an individual adaptation of the material properties according to the specific functions in the device. In this study, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…More promising might be the application of a two-phase material such as nanocrystalline silicon oxide (nc-SiO x :H). In such a material, a columnar nanocrystalline silicon phase providing vertical conductivity is embedded in an amorphous silicon oxide matrix providing enhanced transparency [60,61]. For nc-SiO x :H(n) at the front side of a SHJ solar cell, a slightly higher efficiency compared with an oxide-free nc-Si:H(n) reference is reported [62,63].…”
Section: Loss Mechanisms and Mitigation Strategiesmentioning
confidence: 99%
“…More promising might be the application of a two-phase material such as nanocrystalline silicon oxide (nc-SiO x :H). In such a material, a columnar nanocrystalline silicon phase providing vertical conductivity is embedded in an amorphous silicon oxide matrix providing enhanced transparency [60,61]. For nc-SiO x :H(n) at the front side of a SHJ solar cell, a slightly higher efficiency compared with an oxide-free nc-Si:H(n) reference is reported [62,63].…”
Section: Loss Mechanisms and Mitigation Strategiesmentioning
confidence: 99%
“…Furthermore, nc‐Si:H alloyed with oxygen (nc‐SiO x :H) allows tunable optoelectrical properties, with the advantage of simultaneously obtaining higher E g and lower E a , when compared with a‐Si:H. This unique feature also enables more flexibility to tailor the selective transport for enhancing solar cells performance . Interestingly, with similar optical transparency, n‐type nc‐SiO x :H layers exhibit generally higher conductivity than p‐type layers . Accordingly, the use of p‐type nc‐SiO x :H as a front emitter in SHJ cell, which demands a more sensitive processing than n‐type counterpart, is rarely reported …”
Section: Introductionmentioning
confidence: 99%
“…6 Interestingly, with similar optical transparency, n-type nc-SiO x :H layers exhibit generally higher conductivity than p-type layers. 18,19 Accordingly, the use of p-type nc-SiO x :H as a front emitter in SHJ cell, which demands a more sensitive processing than n-type counterpart, is rarely reported. [20][21][22] On the other hand, in SHJ solar cell application, it is challenging to maintain an excellent electrical cell performance while optimizing the optical layer properties because of the substrate growth selectivity on top of the (i)a-Si:H layer.…”
mentioning
confidence: 99%
“…It has been shown that doped microcrystalline silicon oxide has excellent optoelectronic properties for this application. This material was originally developed for use in thin‐film silicon solar cells, but its versatility as a functional material is clear. A “lab‐on chip” is a miniaturized system designed to perform bio‐analysis faster and more economically than a standard laboratory, at the point of use. Petrucci et al have integrated several of the functions required on to a single glass substrate, including a‐Si:H diode arrays that sense both light (proportional to short‐circuit current) and temperature (proportional to voltage when driven at constant dark current). A non‐volatile memory TFT was fabricated by Sanjeevi et al as a modification of a standard a‐Si:H TFT process.…”
Section: Emerging Applications Of Thin‐film Siliconmentioning
confidence: 99%